Nitrogen-phosphorous co-doped palladium electrocatalyst for glycerol electro-oxidation reaction (GEOR): An efficient system for mesoxalic acid and dihydroxyacetone production - Muhammad Sheraz, Ahmad; Ng, Kim Hoong; Chen, Ching-Lung; Kabir, Faryal; Witoon, Thongthai; Wu, Ta Yeong; Cheng, Chin Kui (Elsevier, 2023)
Electro-oxidation reaction of glycerol (GEOR) is a promising and eco-friendly technique for producing commercially valuable organic acids. In contrast to conventional non-metallic doping into single or multiwalled carbon nanotubes, our work reported the incorporation of N, and P into the Pd/CNTs framework for selective oxidation of glycerol to 1, 3-dihydroxyacetone and mesoxalic acid. Electrochemical and physicochemical characterization showed that the NP doped/PdCNTs has superior electrocatalytic performance for GEOR in alkaline media compared to counter catalysts. NP doped/PdCNTs exhibits better resistivity (If/Ib = 1.71) and requires only 0.09 V electrocatalysis voltage to achieve 76.67 mA cm−2 current density, demonstrating an energy-efficient and cost-competitive method to produce mesoxalic acid and dihydroxyacetone. At 0.09 V vs Ag/AgCl in 0.5 M Gly/0.5 M KOH, the Pd mass activity of NP doped/PdCNTs was 307.30 mAmg-1 Pd, representing 2.45, 1.06, and 1.051 times higher than Pd/CNTs, N doped/PdCNTs, and P doped/PdCNTs, respectively. The yield of 1, 3-dihydroxyacetone was 29.76 times higher than Pd/CNTs, 24.06 times higher than N doped/PdCNTs, and 1.06 times higher than P doped/PdCNTs.